2022
DOI: 10.3389/fimmu.2022.928945
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in the diagnostic algorithm of myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex disease that is mainly diagnosed based on its clinical symptoms. Biomarkers that could facilitate the diagnosis of ME/CFS are not yet available; therefore, reliable and clinically useful disease indicators are of high importance. The aim of this work was to analyze the association between ME/CFS clinical course severity, presence of HHV-6A/B infection markers, and plasma levels of autoantibodies against adrenergic and muscarinic acetylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Additionally, several recent studies have identified higher copy numbers of HHV-6 and EBV in ME/CFS patients compared to healthy controls ( Fevang et al, 2021 ; Lee et al, 2021 ; Gravelsina et al, 2022 ). Lee et al observed an association between HHV-6B and HHV-7 viral load and severity of ME/CFS symptoms by analyzing salivary viral load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several recent studies have identified higher copy numbers of HHV-6 and EBV in ME/CFS patients compared to healthy controls ( Fevang et al, 2021 ; Lee et al, 2021 ; Gravelsina et al, 2022 ). Lee et al observed an association between HHV-6B and HHV-7 viral load and severity of ME/CFS symptoms by analyzing salivary viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al observed an association between HHV-6B and HHV-7 viral load and severity of ME/CFS symptoms by analyzing salivary viral load. Gravelsina et al found a higher viral load of HHV-6B in peripheral blood mononuclear cells (PBMC) corresponding to the severity of ME/CFS symptoms, with 84.2% of patients with severe ME/CFS having a load greater than 1,000 copies per million PBMC compared to 57.1% of patients with mild ME/CFS and 11.1% of health controls ( Gravelsina et al, 2022 ). Fevang et al found a higher average copy number of EBV in the peripheral blood of ME/CFS patients compared to healthy controls, however the difference was not statistically significant ( Fevang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…During dormancy periods [ 139 ], and the IgG levels against HSV-1 are associated with brain fog, AD, schizophrenia, and bipolar disorders [ 140 ]. HHV-6 has also been linked to the development of encephalopathy, ME/CFS and other neurological disorders [ 141 ], and is known to infect CD4 + T-cells preferably, but also CD8 + , macrophages/monocytes and natural killer (NK) cells. HHV-6-infected cells affect immune responses [ 142 ].…”
Section: Myalgic Encephalomyelitis/chronic Fatigue Syndromementioning
confidence: 99%
“…In a recent study, Gravelsina et al provided supportive evidence for the potential association of HHV-6 and ME/CFS and the disease’s autoimmune nature. The study investigated 134 ME/CFS patient serum samples and demonstrated that a higher HHV-6 load was associated with more severe disease and higher HHV-6 loads correlated with higher muscarinic acetylcholine receptor autoantibody levels [ 136 ]. A seminal study by Kasimir et al addressed a crucial shortcoming regarding research into HHV-6’s association with various diseases.…”
Section: Other Autoimmune Diseasesmentioning
confidence: 99%